Surfacing : on being Black and feminist in South Africa - Lewis, Desiree; Baderoon, Gabeba (Wits University Press, 2021)
What do African feminist traditions that exist outside the canon look and feel like? What complex cultural logics are at work outside the centres of power? How do spirituality and feminism influence each other? What are the histories and experiences of queer Africans? What imaginative forms can feminist activism take? Surfacing: On Being Black and Feminist in South Africa is the first collection of essays dedicated to contemporary Black South African feminist perspectives. Leading feminist theorist, Desiree Lewis, and poet and feminist scholar, Gabeba Baderoon, have curated contributions by some of the finest writers and thought leaders. Radical polemic sits side by side with personal essays, and critical theory coexists with rich and stirring life histories. By including writings by Patricia McFadden, Panashe Chigumadzi, Sisonke Msimang, Zukiswa Wanner, Yewande Omotoso, Zoë Wicomb and Pumla Dineo Gqola alongside emerging thinkers, activists and creative practitioners, the collection demonstrates a dazzling range of feminist voices. The writers in these pages use creative expression, photography and poetry in eclectic, interdisciplinary ways to unearth and interrogate representations of Blackness, sexuality, girlhood, history, divinity, and other themes. Surfacing is indispensable to anyone interested in feminism from Africa which, the contributors show, is in vivid and challenging conversations with the rest of the world.